1997
DOI: 10.1002/(sici)1099-0720(199710)11:5<399::aid-acp462>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory: unpleasantness fades faster than pleasantness over time

Abstract: We examined the effects of retention intervals on the recollection of the emotional content of events. Memory for personal events was tested for three retention intervals: 3 months, 1 year, and 4.5 years. Participants made pleasantness ratings both at the time of recording the event and during testing of the events. Analyses of the data show that judgments of pleasantness or unpleasantness of an event became less extreme as retention interval increased. This effect was larger for unpleasant events than for ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
183
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(222 citation statements)
references
References 18 publications
26
183
1
1
Order By: Relevance
“…He found that the affect for unpleasant events faded more than the affect for pleasant events. Nearly three decades later, Walker et al (1997) examined the fading of emotions over time, including a group for a three-month retention interval (43 participants), a group for a one-year interval (6 participants), and one participant at a 4.5-year interval. By 6 This is an Author's Accepted Manuscript of an article published in Memory, epub ahead of print published online:14th February 2014, available online at: http://www.tandfonline.com/10.1080/09658211.2014 recording events on the day that the events occurred, the researchers ensured that the data would not be confounded by an event selection bias.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…He found that the affect for unpleasant events faded more than the affect for pleasant events. Nearly three decades later, Walker et al (1997) examined the fading of emotions over time, including a group for a three-month retention interval (43 participants), a group for a one-year interval (6 participants), and one participant at a 4.5-year interval. By 6 This is an Author's Accepted Manuscript of an article published in Memory, epub ahead of print published online:14th February 2014, available online at: http://www.tandfonline.com/10.1080/09658211.2014 recording events on the day that the events occurred, the researchers ensured that the data would not be confounded by an event selection bias.…”
supporting
confidence: 85%
“…First, the FAB has been documented by numerous researchers, and via numerous methodologies, which have tested many parameters of the phenomenon (Gibbons et al, 2011;Holmes, 1970;Ritchie et al, 2006Ritchie et al, , 2009Walker et al, 1997). Regardless of design or measurement nuances, the data clearly identified the source of the FAB to be in ratings of current affect, not the ratings of initial affect (Landau & Gunter, 2009).…”
Section: Context and Methods Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on fading emotions shows that unpleasant emotions fade more quickly than pleasant emotions over time (Skowronski, Gibbons, Vogl, & Walker, 2004;Walker, Skowronski, Gibbons, Vogl, & Thompson, 2003;Walker, Vogl, & Thompson, 1997). This differential fading of unpleasant and pleasant affect was coined the Fading Affect Bias or FAB by Walker, Skowronski, Gibbons, et al (2003).…”
Section: Introductionsupporting
confidence: 90%
“…These results replicated previous results on the FAB (e.g., Walker et al, 1997), and they extended the FAB to REs and NREs. In addition, the FAB was positively related to spirituality, which is positively related to positive mental health outcomes (Cohen, 2002;Ellison & Fan, 2007;Kim et al, 2004;Underwood & Teresi, 2002).…”
Section: Discussionmentioning
confidence: 99%